Faktor Resiko Pengetahuan Kader Tentang KMS Balita terhadap Keterampilan Menggambar Grafik Pertumbuhan Anak pada KMS Balita oleh Kader Posyandu di Kecamatan Rembang Kabupaten Purbalingga - Mulyono, Condro Hadi; Sunarto, Sunarto (Poltekkes Kemenkes Semarang, 2013)
Background : Health Care Center (Posyandu) revitalization program is aimed to upgrade its function and work performance. The figure of SKDN from month to month is monitored to find out the development of Posyandu’s activities and program in working area. If a cadre make a mistake in weighing children’s growth, it will be resulting in wrong conclusion, wrong information, and it will be ending in the wrong decision related to the next policy. Target Research:To find out the relationship between the Knowledge of Children under Five Health Cards (KMS) Toward the Ability in Drawing the Growth Graphic In Children Health Cards (KMS) in Health Care Center (Posyandu) in Kecamatan Rembang Kabupaten Purbalingga Method : This research uses time approach with cross sectional design and the sample 4362 cadres, sample research are one person from each 62 Posyandus. The process of analysis uses univariat by describing each research variable and bivariat to test the relationship between two variable, they are the variable of knowledge influence and the variable of influenced cadre’s ability. Each variable relatioship uses chi square or Fiher’s Exact Test. Result : Most of cadres are junior high school graduation (52%) have a good knowledge about KMS (73%), but their ability in drawing children growth graphic is lack (87%). There is a relationship between the Knowledge of Children under Five Health Cards (KMS) Toward the Ability in Drawing the Growth Graphic In Children Health Cards (KMS) in Health Care Center (Posyandu) in Kecamatan Rembang Kabupaten Purbalingga Conclusion : There is a relationship between the Knowledge of Children under Five Health Cards (KMS) Toward the Ability in Drawing the Growth Graphic In Children Health Cards (KMS) in Health Care Center (Posyandu) in Kecamatan Rembang Kabupaten Purbalingga